PENGEMBANGAN MEDIA ULAR TANGGA NADA & IRAMA (ARGA DAI) SEBAGAI PENGENALAN MUSIK NUSANTARA UNTUK KELAS IV SEKOLAH DASAR - Tri Hartanti; Muflikhul Khaq; Titi Anjarini (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2022)
This study aims to develop the Snake Scales & Rhythm Media (Arga Dai) as an introduction to Indonesian music for the fourth grade of elementary school, to test the feasibility and effectiveness of the media. Purposive sampling technique was used to determine the research sample. Data collection techniques in research are interviews, questionnaires, tests and documentation. The tests carried out to assess the media include a feasibility test and a media effectiveness test. The data analyzed included the initial data analysis in the form of data normality test (Chi Squared) and final data analysis in the form of t-test and N-gain test. The conclusion in the study is that the product was validated by material experts and obtained a percentage score of 93.75% and by media experts it was obtained a percentage score of 90.62% which was included in the very feasible criteria. The teacher and student questionnaire responses to the media were respectively 95% and 89.32%, or included in the very feasible criteria. The effectiveness of the media is obtained by analyzing the comparison of the acquisition of the initial test and the post-test through paired t-test. The test obtains the value of t_count = 14.68 > t_table = 2.079 then H0 is rejected or Ha is accepted. In the form of a sentence, it is stated that the Snake Ladder & Rhythm media has been tested to be effective and suitable to be used to improve SBdP learning outcomes, especially in the material for Indonesian songs. Suggestions in this study are teachers are expected to be able to develop similar media as a form of innovation in developing learning media.